Light‐Responsive Hierarchically Structured Liquid Crystal Polymer Networks for Harnessing Cell Adhesion and Migration. Issue 27 (5th May 2017) - Koçer, Gülistan; ter Schiphorst, Jeroen; Hendrikx, Matthew; Kassa, Hailu G.; Leclère, Philippe; Schenning, Albertus P. H. J.; Jonkheijm, Pascal
Abstract : Extracellular microenvironment is highly dynamic where spatiotemporal regulation of cell‐instructive cues such as matrix topography tightly regulates cellular behavior. Recapitulating dynamic changes in stimuli‐responsive materials has become an important strategy in regenerative medicine to generate biomaterials which closely mimic the natural microenvironment. Here, light responsive liquid crystal polymer networks are used for their adaptive and programmable nature to form hybrid surfaces presenting micrometer scale topographical cues and changes in nanoscale roughness at the same time to direct cell migration. This study shows that the cell speed and migration patterns are strongly dependent on the height of the (light‐responsive) micrometer scale topographies and differences in surface nanoroughness. Furthermore, switching cell migration patterns upon in situ temporal changes in surface nanoroughness, points out the ability to dynamically control cell behavior on these surfaces. Finally, the possibility is shown to form photoswitchable topographies, appealing for future studies where topographies can be rendered reversible on demand. Abstract : Light‐responsive (dynamic) interfaces on liquid crystal polymer networks present a new way to encode the surface topography of a biomaterial. Photoisomerization of azobenzene molecule conjugated in the network leads to changes in the order of the liquid crystal molecules resulting in volume changes in the illuminated areas, generating predesigned responsive topographical features in order to instruct cell behavior.